QUANTITATIVE AND STEREOISOMERIC DETERMINATION OF LIGHT BIOMARKERS IN CRUDE OIL AND COAL SAMPLES - Berthod A.; Wang X.; Gahm K.H.; Armstrong D.W. (My University, 1998)
Indans and tetralins are considered biological markers (biomarkers). These C9-C11 hydrocarbons are present in small amounts in organic geological samples. Methyl substituted indans or tetralins may possess a stereogenic center (carbon). Thus they can exist as enantiomers and, in the case of disubstituted entities, also as diastereoisomers. The concentrations of 1-methylindan, 1,3-dimethylindan, 1-methyltetralin, and 2-methyltetralin were determined in sixteen crude oil samples of different sources and in fourteen coal samples of different sources and ranks. Deuterated homologues were synthesized as standards to spike the samples and to assure accurate quantitative analysis. A procedure using HPLC fractionation followed by GC/MS analysis allowed the determination of μg/g (ppm) amounts of these compounds in oils. The concentration of substituted indans and tetralins was 3-4 orders of magnitude less in coal than in crude oil. The select ion mass spectrometry (SIM) mode in GC/MS and the deuterated standards allowed detection of the much lower amounts (ng/g, ppb down to pg/g, ppt) of these compounds in coal samples. The stereochemistry of the biomarkers was determined, and the relationship between their relative concentrations and the location and type of the deposits was examined. Racemic mixtures of the indans and tetralins studied were found in all samples of oil and coal. It is postulated that there is an inverse relationship between the retention of stereochemical configuration and the molecular weight of hydrocarbons in crude oil. The chiral retention of configuration cut-off is thought to be between molecular weights of 146 and 208. An excess of cis-1,2-dimethylindan was found in all oil samples (average cis/trans ratio: 3/2). The 2-methyltetralin concentration was found to be about twice that of 1-methyltetralin in all oil and coal samples. Similar concentration correlations were found for the indan derivatives in oils and coals.